2018
DOI: 10.3390/ma11101955
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pallet Mover Safety in the Manufacturing Industry: A Bow-Tie Analysis of Accident Scenarios

Abstract: A Belgian manufacturing company uses pallet movers for internal transport. Despite the company’s efforts to improve occupational safety, accidents with pallet movers remain noteworthy. In order to control occupational accidents, it is crucial to have a clear view of the potential accident scenarios that are present in a company. The bow-tie method is a way to capture and visualize these accident processes in an integrative way. Included in the bow-tie are safety barriers (both technical as organizational and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The methodology that enables organisations to compose a set of company-specific indicators in order to operationalise the observable sub-domains of safety culture has been elaborated in van Nunen et al [ 127 , 128 ]. The methodology consists of five different steps (see Figure 5 ).…”
Section: Assessing the Safety Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The methodology that enables organisations to compose a set of company-specific indicators in order to operationalise the observable sub-domains of safety culture has been elaborated in van Nunen et al [ 127 , 128 ]. The methodology consists of five different steps (see Figure 5 ).…”
Section: Assessing the Safety Culturementioning
confidence: 99%
“…The first step is the identification of possible accident scenarios within the company. In the articles of van Nunen et al [ 127 , 128 ], the use of the bow-tie method is explained in-depth as a suitable method to make an inventory of possible accident scenarios, taking into account the specific context of an organisation. When using this bow-tie approach, a comprehensive and detailed overview can be composed of possible causes and consequences of potential incidents within a company.…”
Section: Assessing the Safety Culturementioning
confidence: 99%
“…An example of a risk assessment tool is the bowtie (BT) analysis, which visually presents the risk factors leading to an unwanted event and the impacts that might result from the unwanted event as well as the controls or safety barriers that could be deployed to prevent and mitigate the unwanted event (Culwick, Merry, Clarke, Taraporewalla, & Gibbs, 2016;Van Nunen et al, 2018). The BT analysis can be accompanied by an AcciMap (Forbes, Heitman, & McCulloch, 2020) to highlight the individuals or parties who are responsible for ensuring the reliability of the controls (Tabibzadeh, Stavros, Ashtekar, & Meshkati, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, several studies have revealed that some factors such as environmental conditions with a significant presence of dust, humidity, and falling rocks can act as precursor agents to accidents in underground mining, increasing the incidence and severity of accidents [22,23,24,25,26]. Hence, it is important for the stakeholders involved in the industry to have the proper tools, frameworks, and understanding of the hazards to deal with accident causation and to achieve a proper safety system [7,27].…”
Section: Introductionmentioning
confidence: 99%